Faktor Sosial dan Budaya yang Membentuk Stigma Terhadap Pria Pengguna Skincare dalam Konstruksi Maskulinitas Modern - Muhamad Haikal Davin; Mirna Nur Alia; Rika Sartika (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The increasing use of skincare products among men has become a growing phenomenon in modern society. However, this trend is still often accompanied by negative stigma rooted in traditional masculine norms that associate self-care practices with femininity. This study aims to analyze the social and cultural factors that shape stigma toward men who use skincare products within the construction of modern masculinity. This research employed a Systematic Literature Review (SLR) method by reviewing national and international journal articles published between 2020–2025. Data were collected through Google Scholar, Scopus, ScienceDirect, and Garuda using keywords related to male skincare, masculinity, stigma, and self-care. The findings reveal four main factors influencing stigma toward male skincare users: patriarchal culture and traditional masculinity, pressure from family and peer groups, the influence of social media, and shifting perceptions of skincare as a form of self-care. The study concludes that masculinity is dynamic and continuously negotiated amidst social and cultural changes. Skincare is increasingly viewed not as a symbol of femininity, but as part of health awareness and modern male identity